Meticulous cecal image documentation at colonoscopy is associated with improved polyp detection - Mo Hameed Thoufeeq; Bjorn Joakim Rembacken (Endoscopy International Open, 2015)
Background and study aims: No studies have looked at the quality of cecal images versus the outcomes of colonoscopic procedures. Here, we tested our hypothesis that endoscopists who provide better image documentation of the cecum during their procedures have a higher polyp detection rate (PDR). Patients and methods: In this retrospective study, planned colonoscopies performed by 16 experienced colonoscopists were included. We formulated a new scoring system, the cecal image documentation score (CIDS), for quantifying the quality of the cecal images obtained at colonoscopy. Cecal image documentation was graded as follows: no image, 0; unclear image, 1; clear image, 2; clear image with a label, 3. We assessed the correlation between image quality and the PDR. Results: A total of 651 procedures performed by 16 colonoscopists were analyzed retrospectively. The mean CIDS for the 16 endoscopists was 2.13. The mean PDR was 23.5 %, and the mean polyps per procedure value (PPP) was 0.42. The 10 colonoscopists with a mean CIDS > 2.0 (n = 429 procedures) had a PDR of 27.8 % and a PPP of 0.51. On the other hand, the 6 colonoscopists (n = 222 procedures) with a mean CIDS < 2.0 had a PDR of 15.2 % and a PPP of 0.23. A mean CIDS > 2.0 was associated with a higher PDR (odds ratio [OR] 2.1, 95 % confidence interval [CI] 1.4 – 3.2, P = 0.001). A mean CIDS > 2.0 was found to be an independent predictor of a higher PDR (OR 2.53, 95 %CI 1.45 – 3.59, P = 0.001). A mean CIDS > 2.0 was also associated with a higher right-sided PDR (OR 3.67, 95 %CI 1.91 – 7.02, P < 0.001). Conclusions: Colonoscopists who are more meticulous in cecal image documentation detect more polyps per procedure and have higher PDRs. Better cecal image documentation is also associated with better right-sided colonic polyp detection.